Health Promoting-behaviors and its Relation with the Risk of Type 2 Diabetes in Women Referred to Community Health Centers in Rasht - Leila Mirhadyan; Sekineh Molaee; Homa Mosaffay Khomami; Ehsan Kazem Nejad Leili (Golestan University of Medical Sciences, 2019)
Background and objectives: Diabetes is the most common metabolic disease in developing countries. Because the cause of many chronic diseases lies in the human's lifestyle, performing health promotion behaviors is the best way to maintain and improve the health. Hence, this study aimed to compare the health promoting behaviors based on the Pender model in at risk groups of type 2 diabetes in women referred to health centers of Rasht city 2017. Methods: This cross-sectional and analytical-descriptive study was performed on 300 women referring to community health centers of Rasht city and was conducted by stratified random sampling method. Data was collected by Health-Promoting Lifestyle Profile-II (HPLP-II) Questionnaire and the questionnaire evaluating the risk of type 2 diabetes using the FINDRISK tool .Data analysis  was performed by SPSS version 21 using ANOVA test, Tukey test and independent T-test. Results: The mean score and standard deviation of health promotion behaviors in this study have been varied from 144.18 ± 19.56 in the low risk group and 129.27±17.86 in the very high-risk group of type 2 diabetes. The difference in score of health promotion behaviors dimensions in the five groups according to the risk of type 2 diabetes, except the interpersonal relationships dimension, was statistically significant (P< 0.05). Conclusion: The high risk and very high risk groups than low risk and very low risk of type 2 diabetes had less scores of health promoting behaviors. In other words, people with a healthier lifestyle were less likely to develop type 2 diabetes .